Differences of Retinal Blood Flow Between Arteries and Veins Determined by Laser Speckle Flowgraphy in Healthy Subjects - Iwase, Takeshi; Ra, Eimei; Yamamoto, Kentaro; Kaneko, Hiroki; Ito, Yasuki; Terasaki, Hiroko (Medicine (Baltimore), 2015)
To characterize the total retinal blood flow determined by laser speckle flowgraphy (LSFG) of healthy subjects.This prospective cross-sectional study was conducted at the Nagoya University Hospital. One hundred fifteen right eyes of 115 healthy subjects (mean age: 39.4 ± 16.1 years) were studied. The total blood flow in the retinal arteries and veins around the optic nerve head was measured separately using the total retinal flow index (TRFI), which represents blood flow volume. The lumen diameters of the retinal vessels determined by LSFG and by adaptive optics (AO) camera were compared. The images obtained by LSFG and AO camera were merged, and the distribution of the mean blur rates (MBRs), which represent the velocities of the erythrocytes, was evaluated on the images.The mean TRFI in veins (1812 ± 445, arbitral units) was significantly higher than that in arteries (1455 ± 348, arbitral units; P < 0.001). Linear regression analysis showed a significant correlation between the TRFI in the arteries and veins (P < 0.001). Linear regression analysis also showed a highly significant correlation between the diameters of arteries and veins determined by LSFG and by the AO camera (arteries, r = 0.94, P < 0.001; veins, r = 0.92, P < 0.001). The ratios of the lumen diameters determined by LSFG to that by AO camera was significant lower in arteries (0.068 ± 0.005, arbitral units) than in veins (0.074 ± 0.007, arbitral units) (P < 0.001). The MBRs of veins were homogeneous throughout the width of the lumen; however, the MBRs in the arteries were higher at the center and lower close to the walls of the lumen.The higher TRFIs in the veins than in the arteries indicate that there is a smaller volume of retinal blood flow in arteries than veins. However, the possibility remains that LSFG has inherent problem that the arterial lumen diameter determined by LSFG is smaller than actual one because of the characteristics of arteries. This would result in a smaller volume of retinal blood flow in the arteries than veins in LSFG.